Penerapan Algoritma Bee Colony Untuk Optimasi Rute Wisata Pulau Belitung - Dilaga, Adena Jaya (STMIK Budi Darma, 2019)
The number of tourist attractions on Belitung Island that can be reached makes it difficult for travelers to find the optimum route, both in terms of distance, time, and costs incurred to travel from one tourist spot to another. One of the factors that influence the amount of expenditure when traveling is transportation costs. The thing that is closely related to transportation is the distance traveled, too much waste of time on the way to the tourist attractions due to the wrong choice in the route taken. Based on the existing problems, optimization is needed in finding the optimum route from the initial position to the destination position using the Bee Clony Algorithm.